1997
DOI: 10.1038/bjc.1997.295
|View full text |Cite
|
Sign up to set email alerts
|

A comet assay of DNA damage and repair in K562 cells after photodynamic therapy using haematoporphyrin derivative, methylene blue and meso-tetrahydroxyphenylchlorin

Abstract: Summary Single-cell electrophoresis (comet assay) has been used to evaluate DNA damage and repair in the human myeloid leukaemia cell line K562 after low-dose (predominantly sub-lethal) treatments of hyperthermia and photodynamic therapy (PDT). Three different photosensitizers were examined: haematoporphyrin derivative (HpD), methylene blue (MB) and meso-tetrahydroxyphenylchlorin (mTHPC). None of the drugs in the absence of light, nor in light alone, resulted in detectable DNA damage. However, a significant am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 31 publications
1
31
1
Order By: Relevance
“…Since our data are in contrast to in-vitro studies in human myeloid leukaemia and nasopharyngeal carcinoma cells where no DNA damage was found after mTHPC-PDT [33,34], the observed effect may depend on cell line.…”
Section: Discussioncontrasting
confidence: 54%
“…Since our data are in contrast to in-vitro studies in human myeloid leukaemia and nasopharyngeal carcinoma cells where no DNA damage was found after mTHPC-PDT [33,34], the observed effect may depend on cell line.…”
Section: Discussioncontrasting
confidence: 54%
“…Oxidative damage leading to single-strand breaks and alkali-labile sites, DNA-protein crosslinks and DNA degradation, as well as to chromosome aberrations has been reported (Evans et al, 1997; Oleinick and Evans, 1998). These lesions, however, are likely to be relatively easily repaired (McNair et al, 1997). Considering that MMR seems not to be affected by PDT, it is reasonable to assume that PDTinduced DNA damage remains of low clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,15,20-meta-tetra-(hydroxyphenyl)chlorin (m-THPC) is a neutral lipophilic second-generation photosensitiser with an absorption maximum at 652 nm. Confocal laser scanning fluorescence microscopy studies of m-THPC in vitro have shown a diffuse distribution of the drug in the cytoplasm (McNair et al, 1997). Although there is no localisation of the photosensitiser within the nucleus, a low level of potentially mutagenic DNA damage could occur, depending on the photosensitiser, the cellular repair mechanisms and the affected genes (Oleinick and Evans, 1998).…”
mentioning
confidence: 99%
“…The mechanisms of DNA damage induced by photodynamic therapy are not well known. PDT can cause cross-linking of DNA strands (McNair et al, 1997, Haylett et al, 2003, Woods et al, 2004. DNA damage caused by photodynamic therapy may occur in cancer cells and normal cells surrounding the tumor.…”
Section: Changes In Dnamentioning
confidence: 99%